Methods for testing and evaluating survey questionnaires - Presser, Stanley (Wiley-Interscience, 2004)
The definitive resource for survey questionnaire testing and evaluation Over the past two decades, methods for the development, evaluation, and testing of survey questionnaires have undergone radical change. Research has now begun to identify the strengths and weaknesses of various testing and evaluation methods, as well as to estimate the methods’ reliability and validity. Expanding and adding to the research presented at the International Conference on Questionnaire Development, Evaluation and Testing Methods, this title presents the most up-to-date knowledge in this burgeoning field. The only book dedicated to the evaluation and testing of survey questionnaires, this practical reference work brings together the expertise of over fifty leading, international researchers from a broad range of fields. The volume is divided into seven sections: Cognitive interviews Mode of administration Supplements to conventional pretests Special populations Experiments Multi-method applications Statistical modeling Comprehensive and carefully edited, this groundbreaking text offers researchers a solid foundation in the latest developments in testing and evaluating survey questionnaires, as well as a thorough introduction to emerging techniques and technologies.
Wiley series in survey methodology
Keywords: Social Sciences; sociologie; sociální vědy